Are two commonly used self-report questionnaires useful for identifying antihypertensive medication nonadherence?. Issue 5 (May 2015) - Gallagher, Benjamin D.; Muntner, Paul; Moise, Nathalie; Lin, Jenny J.; Kronish, Ian M.
Abstract : Objective: Medication nonadherence is a major cause of uncontrolled hypertension, but clinicians are poor at judging adherence, and the gold standard for measuring adherence, electronic monitoring, is rarely available in clinical settings. Self-report questionnaires (SRQs), by contrast, are inexpensive, easy to administer, and hence, may be useful for 'diagnosing' nonadherence. In this study, we evaluated the validity of two commonly used medication adherence SRQs among patients with uncontrolled hypertension, using electronic pillbox measurement as the gold standard. Methods: A total of 149 patients with uncontrolled hypertension had adherence to their antihypertensive medication regimen monitored using a four-compartment electronic pillbox (MedSignals) between two primary care visits (median 50 days). Participants completed the 8-item Morisky Medication Adherence Scale (MMAS-8) and the Visual Analog Scale (VAS) at the second visit. Likelihood ratios were calculated using less than 80% correct dosing adherence by electronic measurement as the gold standard. Results: SRQ scores indicating low adherence (MMAS-8 <6 and VAS <80%, 23 and 9% of participants, respectively) had likelihood ratios of 2.00 [95% confidence interval (CI) 1.10–3.65] and 7.72 (95% CI 1.77–33.6), respectively, for detecting nonadherence compared to electronic measurement. SRQ scores indicating highest adherence (MMAS-8 = 8 and VAS = 100%, 43 and 61% of participants, respectively) had likelihood ratios of 0.55 (95% CI 0.35–0.85) and 0.76 (95% CI 0.57–1.01), respectively, for detecting nonadherence. Conclusion: The MMAS-8 and VAS are modestly useful in identifying antihypertensive medication nonadherence. Other tools, including electronic measurement, may be needed to guide titration of antihypertensive medications among patients with uncontrolled hypertension.